Improvement of Manure Management for Crop Production in Central Uganda - Zake, J.; Tenywa, J. S.; Kabi, F. (Journal of Sustainable Agriculture, 2010)
Manure management practices in sub-Saharan Africa vary depending on the importance smallholder farmers attach to its use as a soil amendment. Cattle manure, which is the primary on-farm manure resource, is generally of low quality due to poor manure management practices. The objective of this study was to improve cattle manure quality on-farm in terms of plant nutrient conservation and enhancement. The study involved two cattle management systems, namely intensive (IS) and semi-intensive (SEI). The study involved eight smallholder farms selected through purposely random sampling and were treated as replicates. The farms were located in Lukwanga parish, Wakiso district, Central Uganda. Each farm under the IS had an average of two heads of mainly Friesian breed of cattle whereas those under the SEI system had an average of three heads of local breed cattle. Other variables include seasonal changes and manure management practices (including farmers practice and improved management practices). Composted manure from both practices was applied at rates of 0 and 2.5 t ha−1 in a field experiment conducted on the same eight smallholder farms as replicates to evaluate performance using Longe 1 maize as the test crop. Cattle manure quality was significantly (p < 0.05) superior during the wet season to that of the dry season in terms of total organic carbon (OC), nitrogen (N), phosphorus (P), and potassium (K+). In both seasons, the IS manure quality was consistently higher (p < 0.05) than that of SEI irrespective of the season. Furthermore, the IS generated more manure (p < 0.05) per cattle unit than its SEI counterpart irrespective of the season. The manure from improved management practices, which involved collection of cattle dung every day and heaping it under the shade of a tree until enough material accumulated to enable its preparation for crops, performed considerably better (p < 0.05) than the farmers’ manure management practice in terms of cattle manure quality. Under the IS and SEI, the improved manure management practice was greater by 48% and 55%; 36% and 21%; 42% and 52%; 67% and 44% for total OC, total N, total P, and total K+, respectively. Improved manure management practices increased maize grain yields significantly by (p < 0.05) by 10% and 18%, respectively, compared with that generated from farmer’s manure management practice under IS and SEI. A similar trend was noted for maize dry matter yields from improved cattle manure applied at rates of 2.5 t ha−1 under both cattle management systems, hence a significant (p < 0.05) increase of 50% and 44% above the control treatment (no manure application) under IS and SEI, respectively.
Keywords: Cattle manure; Intensive and Semi-intensive cattle management; Manure management